Circulating Serum MicroRNAs as Potential Diagnostic Biomarkers of Posttraumatic Stress Disorder: A Pilot Study - Snijders, Clara; Krauskopf, Julian; Pishva, Ehsan; Eijssen, Lars; Machiels, Barbie; Kleinjans, Jos; Kenis, Gunter; van den Hove, Daniel; Kim, Myeong Ok; Boks, Marco P. M.; Vinkers, Christiaan H.; Vermetten, Eric; et al. (Frontiers in Genetics, 2019)
Post-traumatic stress disorder (PTSD) is a psychiatric disorder that can develop upon exposure to a traumatic event. While most people are able to recover promptly, others are at increased risk of developing PTSD. However, the exact underlying biological mechanisms of differential susceptibility are unknown. Identifying biomarkers of PTSD could assist in its diagnosis and facilitate treatment planning. Here, we identified serum miRNAs of subjects that underwent a traumatic event and aimed to assess their potential to serve as diagnostic biomarkers of PTSD. Next generation sequencing was performed to examine circulating miRNA profiles of 24 members belonging to the Dutch military cohort PRISMO. Three groups were selected: “susceptible” subjects who developed PTSD after combat exposure, “resilient” subjects without PTSD, and non-exposed control subjects (N=8 per group). Differential expression analysis revealed 123 differentially expressed miRNAs in PTSD subjects compared to controls, and 4 in PTSD subjects compared to resilient individuals (after multiple testing correction and a log2 FC cut off of ≥ |1|). Weighted Gene Co-expression Network Analysis (WGCNA) identified a module of co-expressed miRNAs which could distinguish between the three groups. In addition, Receiver Operating Characteristic (ROC) curve analyses suggest that the miRNAs with the highest module memberships could have a strong diagnostic accuracy as reflected by high areas under the curves. Overall, the results of our pilot study suggest that serum miRNAs could potentially serve as diagnostic biomarkers of PTSD, both individually or grouped within a cluster of co-expressed miRNAs. Larger studies are now needed to validate and build upon these preliminary findings.